2011
DOI: 10.1111/j.1447-0756.2011.01677.x
|View full text |Cite
|
Sign up to set email alerts
|

Causes of primary amenorrhea: A report of 295 cases in Thailand

Abstract: The present study has currently been the largest case series of primary amenorrhea. Müllerian agenesis is the most prevalent cause in our study, while gonadal dysgenesis is the most common cause in the largest-scale study in the USA. Hence, racial, genetic and environmental factors could play roles in the cause of primary amenorrhea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 10 publications
5
33
2
2
Order By: Relevance
“…In our study müllerian agenesis (58.17 %) was the most common cause which was compatible with Tanmahasamut et al (Thailand). 4 This is in contrast to American study by Reindollar et al 5 gonadal dysgenesis was commonest (48.5%) -American study. This verified that racial and environmental factors played an essential part in the causes of primary amenorrhea.…”
Section: Resultscontrasting
confidence: 54%
See 1 more Smart Citation
“…In our study müllerian agenesis (58.17 %) was the most common cause which was compatible with Tanmahasamut et al (Thailand). 4 This is in contrast to American study by Reindollar et al 5 gonadal dysgenesis was commonest (48.5%) -American study. This verified that racial and environmental factors played an essential part in the causes of primary amenorrhea.…”
Section: Resultscontrasting
confidence: 54%
“…Genetic (39%) and anatomic abnormalities (42%) appear to be remarkable cause of primary amenorrhea. 4 The true incidence of obstructive Müllerian anomalies is unknown, but is believed to be between 0.1% and 3.8%. Incomplete canalization of the urogenital sinus with the Müllerian system can lead to imperforate hymen.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, our observations were similar to a study conducted in Thailand by Tanmahasamut P et al, where they analyzed 295 cases of primary amenorrhea and found that the most common cause was Mullerian agenesis (39.7%), followed by gonadal dysgenesis (35.3%). 4 A Srilankan study published by Samarakoon et al also showed incidence of gonandal dysgenesis as 20.6% in patients with primary amenorrhoea. 5 Hence, racial and environmental factors may have role in the aetiology of primary amenorrhea.…”
Section: 2mentioning
confidence: 99%
“…[3][4][5][6] Therefore through this audit we aim to empower the medical practitioners in developing countries to effectively evaluate a patient with primary amenorrhoea and help determine the best management line and implement it.…”
Section: Introductionmentioning
confidence: 99%
“…Среди причин гипоэстрогении у женщин молодого возраста можно назвать центральный (гипогонадотроп-ный) гипогонадизм, который выявляется примерно у 10% женщин с первичной аменореей [5,6] и у 35% женщин со вторичной аменореей [7,8]. Гипоэстрогения при гонадо-тропной недостаточности оказывает негативное влияние на здоровье пациенток даже в молодом возрасте, что про-является атерогенными изменениями липидов, потерей минеральной плотности кости, повышением уровня тре-вожности и депрессии [9,10].…”
unclassified